The Effect Of Job Description On Employee Performance At The Office Of The Regional Revenue Agency Of Tual City - Ahmad Faqih Zulfikar; Sri Andayaningsih; H. A.Muhiddin Daweng (International Journal of Economic Research and Financial Accounting, 2024)
This study aims to determine the effect of Job Description on employee performance at the Tual City Regional Revenue Agency Office. The types of data used in this study are primary data and secondary data. The research instrument used in this study used the Likert scale method. Based on the results of data research using statistical calculations through the Statistical for the Social Science (SPSS) application regarding the Effect of Job Description on Employee Performance, the author can conclude that Variable X, namely Job Description, has a positive and significant effect on Employee Performance with a Job Description (X) coefficient value of 0.393 and a calculated t value of 2,836 t > table 2.021 with a significant value of 0.007 < 0.05.